2007
DOI: 10.1677/joe-06-0042
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of 11β-hydroxysteroid dehydrogenase 1 in human orbital adipose tissue: a comparison with subcutaneous and omental fat

Abstract: Glucocorticoids (GCs) have a profound effect on adipose biology increasing tissue mass causing central obesity. The pre-receptor regulation of GCs by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) that activates cortisol from cortisone has been postulated as a fundamental mechanism underlying the metabolic syndrome mediating adipocyte hyperplasia and hypertrophy in the omental (OM) depot. Orbital adipose tissue (OF) is the site of intense inflammation and tissue remodelling in several orbital inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Messenger RNA levels of this receptor were found to be higher in omental than in subcutaneous adipose tissue in some, but not all, studies [6,10,[19][20][21]. Negative associations between GR␣ mRNA expression and adiposity measures were previously reported [6,19].…”
Section: Introductionmentioning
confidence: 81%
“…Messenger RNA levels of this receptor were found to be higher in omental than in subcutaneous adipose tissue in some, but not all, studies [6,10,[19][20][21]. Negative associations between GR␣ mRNA expression and adiposity measures were previously reported [6,19].…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies suggested that increased serum cortisol level in men is mainly mediated through 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1) activity [24,25]. 11b-HSD1is a bidirectional enzyme, located in the abdominal fat mass and omental subcutaneous tissue, and mediates the conversion of cortisone to cortisol [26,27] thermore there are gender di erences in 11b-HSD1 activity, which is greater in men [20], and 5a-reductase activity, which is greater in women [28]. is di erence in enzyme activity may result in an increase in serum cortisol levels in men and would alter its degree of correlation with parameters associated with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Ilankovan and Soames22 found comparable relative volumes of collagen and endothelial cells, as well as the density of mast cells between orbital and buccal fat, which were significantly different from those in subcutaneous fat from non-TAO patients. Another study found that adipocytes from the orbit were significantly smaller in area, maximum diameter and perimeter than adipocytes from omental and subcutaneous adipose tissues in non-obese (BMI <25 kg/m 2 ) patients 23. The authors also showed higher expression of CD68 and glucocorticoid receptor alpha in orbital adipocytes than in omental and subcutaneous adipocytes.…”
Section: Discussionmentioning
confidence: 90%